Casimir effect in Podolsky electrodynamics: A functional approach - Barone, F. A.; Nogueira, A. A. [UNESP]; Mostepanenko, V. M.; Petrov, V. M. (World Scientific Publ Co Pte Ltd, 2016)
In this work we study the Podolsky electrodynamics in the presence of conducting surfaces. We calculate the classical interaction between one perfect conducting plate and one point charge. We also consider the interaction between two parallel conducting plates.
Keywords: Classical field theories; theory quantized fields